038. Association Between High Body Mass Index and Smoker in Shopkeepers with Chronic Venous Insufficiency in Sederhana Market Bandung - Pertiwi, Dista Yuristia; Djajakusumah, Teguh Marfen (JBN (Jurnal Bedah Nasional), 2024)
Background : Chronic venous insufficiency (CVI) is a condition that encompasses several pathological changes such as lower extremity edema, skin trophic changes, and discomfort than secondary to venous hypertension. It is estimated that 73% of women and 56% of men are affected by CVI. Shopkeepers are the jobs that have a high risk of becoming a risk factor for CVI such as high BMI > 25 (body mass index) and smokers. The study aims to know the association between high BMI and smoker in shopkeepers with CVI in the Sederhana Market, Bandung. Methods: The cross-sectional study was conducted on shopkeepers in the Sederhana Market from March to September 2023. Data from shopkeepers that met the inclusion criteria was collected through history taking, physical examination, and filling out the research questionnaire. Results : Among 48 shopkeepers in Sederhana Market, 37 had CVI (79.2%), with a demographic of 73% male and 27% female, and the mean age of the patients was 44.9 (30-59) years. The average sitting time during trading was 15.1 (10-20) hours, and the average standing time during trading was 5.3 (2-13) hours. The association between high BMI and smoker with CVI in shopkeepers was carried out, and it was found that there was a association between high BMI (p = 0.0006), and smokers (p = 0.0023) with CVI among the shopkeepers. Conclusion: There are association between high BMI and smoker in shopkeepers with CVI in the Sederhana Market, Bandung.